Oxidative stress‐related DNA damage and homologous recombination repairing induced by N, N‐dimethylformamide. Issue 7 (21st September 2015) - Wang, Cui; Yang, Jinhuan; Lu, Dezhao; Fan, Yongsheng; Zhao, Meirong; Li, Zhuoyu
Abstract: The intensified anthropogenic release of N, N ‐dimethylformamide (DMF) has been proven to have hepatotoxic effects. However, the potential mechanism for DMF‐induced toxicity has rarely been investigated. Our research implicated that DMF induced a significantly dose‐dependent increase in reactive oxygen species (ROS) in HL‐7702 human liver cells. Moreover, oxidative stress‐related DNA damage, marked as 8‐hydroxy‐2′‐deoxyguanosine, was increased 1.5‐fold at 100 mmol l –1 . The most severe DNA lesion (double‐strand break, DSB), measured as the formation of γH2AX foci, was increased at/above 6.4 mmol l –1, and approximately 50% of cells underwent DSB at the peak induction. Subsequently, the DNA repair system triggered by molecules of RAD50 and MRE11A induced the homologous recombination (HR) pathway by upregulation of both gene and protein levels of RAD50, RAD51, XRCC2 and XRCC3 at 16 mmol l –1 and was attenuated at 40 mmol l –1 . Consequently, cellular death observed at 40 mmol l –1 was exaggerated compared with exposure at 16 mmol l –1 . Although the exact mechanism relying on the DMF‐induced hepatotoxicity needs further clarification, oxidative stress and DNA damage involved in DSBs partially explain the reason for DMF‐induced liver injury. Oxidative stress‐induced DNA damage should be first considered during risk assessment on liver‐targeted chemicals. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Our study demonstrated for the first time that DMF reduced the proliferation of human liver cells by causing oxidative DNA damage and double‐strand breaks through the release of reactive oxygen species during biodegradation. Moreover, the ineffectiveness of the homologous repair pathway, leading to persistent DNA lesions, can partially explain the reason for DMF‐related liver injury.